L-shell X-Ray conversion yields for laser-irradiated tin and silver foils - Singh,RL; White,S; Charlwood,M; Keenan,FP; Hyland,C; Bailie,D; Audet,T; Sarri,G; Rose,SJ; Morton,J; Baird,C; Spindloe,C; et al. (Laser and Particle Beams, 2022)
We have employed the VULCAN laser facility to generate a laser plasma X-ray source for use in photoionization experiments. A nanosecond laser pulse with an intensity of order 1015 Wcm−2 was used to irradiate thin Ag or Sn foil targets coated onto a parylene substrate, and the L-shell emission in the 3.3–4.4 keV range was recorded for both the laser-irradiated and nonirradiated sides. Both the experimental and simulation results show higher laser to X-ray conversion yields for Ag compared with Sn, with our simulations indicating yields approximately a factor of two higher than those found in the experiments. Although detailed angular data were not available experimentally, the simulations indicate that the emission is quite isotropic on the laser-irradiated side but shows close to a cosine variation on the nonirradiated side of the target as seen experimentally in the previous work.